Seasonal Differences and Variability of Concentrations, Chemical Composition, and Cloud Condensation Nuclei of Marine Aerosol Over the North Atlantic. Issue 19 (25th September 2020) - Saliba, Georges; Chen, Chia‐Li; Lewis, Savannah; Russell, Lynn M.; Quinn, Patricia K.; Bates, Timothy S.; Bell, Thomas G.; Lawler, Michael J.; Saltzman, Eric S.; Sanchez, Kevin J.; Moore, Richard; Shook, Michael; et al.
Abstract: The majority of the aerosol particle number (condensation nuclei or CN) in the marine boundary layer (MBL) consists of sulfate and organic compounds that have been shown to provide a large fraction of the cloud condensation nuclei (CCN). Here we use submicron non‐refractory Aerosol Mass Spectrometer (AMS) and filter measurements of organic and sulfate components of aerosol particles measured during four North Atlantic Aerosol and Marine Ecosystems Study (NAAMES) research cruises to assess the sources and contributions of submicron organic and sulfate components for CCN concentrations in the MBL during four different seasons. Submicron hydroxyl group organic mass (OM) correlated strongly to sodium concentrations during clean marine periods ( R  = 0.9), indicating that hydroxyl group OM can serve as a proxy for sea‐spray OM in ambient measurements. Sea‐spray OM contributed 45% of the sum of sea‐spray OM and sea salt during late spring (biomass climax phase) compared to <20% for other seasons, but the seasonal difference was not statistically significant. The contribution of non‐combustion sources during clean marine periods to submicron OM was 47 to 88% and to non‐sea‐salt sulfate 31 to 86%, with likely sources being marine and biogenic. The remaining submicron OM and sulfate were likely associated with ship or continental sources, including biomass burning, even during clean marine periods. The seasonal contribution from secondary sulfate and OM components to submicron aerosol mass was highest during late spring (60%), when biogenic emissions are expected to be highest, and lowest during winter (18%). Removing submicron sea‐spray OM decreased CCN concentrations by <10% because of competing effects from increased hygroscopicity and decreased particle size. During all seasons, adding biogenic secondary sulfate increased hygroscopicity, particle size, and CCN concentrations at 0.1–0.3% supersaturations by 5–66%. The largest change was during early spring when the fraction of hygroscopic sulfate components in the 0.1–0.2 μm size range was highest (80%). During continental periods, the increased contribution from low‐hygroscopicity organic components to 0.1–0.2 μm diameter particles reduces the CCN/CN by 20–100% for three seasons despite the increased CN and mass concentrations. These results illustrate the important role of the chemical composition of particles with diameters 0.1–0.2 μm for controlling CCN in the MBL. Key Points: Ambient hydroxyl group mass correlated strongly to sodium, and their ratio for the limited samples available correlated to dissolved organic carbon normalized by salinity for generated sea spray aerosol Non‐combustion, likely secondary biogenic, sources contribute 47–88% of submicron organic mass and 21–86% of submicron sulfate during marine periods The fraction of particles in the 0.1–0.2 μm size range that were cloud condensation nuclei was highest during early spring due to a larger fraction of hygroscopic sulfate